Reinforcement of hiatal defect repair with absorbable mesh fixed with non-permanent devices. Issue 5 (October 2014) - Silecchia, Gianfranco; Iossa, Angelo; Cavallaro, Giuseppe; Rizzello, Mario; Longo, Fabio
Abstract Aim : To report the results of an open label prospective study on a new technique for laparoscopic hiatal hernia (HH) repair with absorbable mesh fixed with absorbable materials Methods: From January 2011 to May 2013, 43 patients were treated; group A, 20 patients submitted to laparoscopic sleeve gastrectomy (LSG); group B, 13 patients submitted to revisional surgery for the diagnosis of HH and symptomatic GERD post-LSG; and group C, ten patients submitted to 360° fundoplication. All patients underwent cruroplasty reinforced with bio-absorbable mesh fixed with absorbable tacks and/or fibrin glue. Conversion rate, intra-operative complications, operative time (tacks vs tacks plus fibrin glue), perioperative complications, perioperative symptoms and radiological control set the criteria for clinical/surgical evaluation. Results: Conversion and mortality rate was 0%. The mean time for mesh fixation with the tacks vs tacks plus fibrin glue was 6.2 ± 2 vs 7.3 ± 3 min. The remission of GERD symptoms was observed in 39 patients, and we did not observe any cases of mesh-related complications at a mean follow-up of 17.4 months. Recurrence rate was 2.3% (one asymptomatic patient of group B). Conclusions: Reinforcement with absorbable mesh-cancel bio mesh is a safe and effective option for laparoscopic HH repair in normal weight and obese patients.